Olfactory epithelium histopathological findings in long-term coronavirus disease 2019 related anosmia. Issue 12 (16th December 2020) - Vaira, L A; Hopkins, C; Sandison, A; Manca, A; Machouchas, N; Turilli, D; Lechien, J R; Barillari, M R; Salzano, G; Cossu, A; Saussez, S; De Riu, G
Abstract: Background: Olfactory dysfunction represents one of the most frequent symptoms of coronavirus disease 2019, affecting about 70 per cent of patients. However, the pathogenesis of the olfactory dysfunction in coronavirus disease 2019 has not yet been elucidated. Case report: This report presents the radiological and histopathological findings of a patient who presented with anosmia persisting for more than three months after infection with severe acute respiratory syndrome coronavirus-2. Conclusion: The biopsy demonstrated significant disruption of the olfactory epithelium. This shifts the focus away from invasion of the olfactory bulb and encourages further studies of treatments targeted at the surface epithelium.